The Impact of Fiscal Policy on Happiness Levels in ASEAN Countries + South Korea - Muhamad Firdaus; Siti Aisyah (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the impact of fiscal policy and macroeconomic indicators on the happiness index in the ASEAN region and South Korea. This study fills a gap in the literature by dissecting fiscal policy into two dimensions: tax burden (Tax Ratio) and tax composition (Tax Structure), and includes South Korea as a benchmark for developed countries to increase model variation and complementarity Methodology: Using panel data regression with the Fixed Effects Model (FEM) approach on data from 2015-2022 Results: this study found that per capita income (GDP) and tax ratio have a positive and significant effect on happiness. These findings indicate that people are willing to bear a higher tax burden, but only if the fiscal policy is well utilized. Applications/Originality/Value: These findings suggest that policymakers should focus on inclusive economic growth and the effectiveness of public spending to improve the subjective well-being of the people.